Analisis Rencana Proses Picking pada Distrubution Center Toko X Menggunakan 5 Whys dan Siklus PDCA - Ndari, Retno Ulan; Akbardin, Juang; Wulansari, Dwi Novi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
The Distribution Center (DC) of Toko X plays a crucial role in the logistics system of a minimarket retail company, ensuring the delivery of goods to branch stores. Despite having a structured picking process supported by pick-to-light technology, discrepancies in item quantities—referred to as picking variances—continue to occur. This study was conducted through direct observation and interviews with warehouse staff, followed by a root cause analysis using the 5 Whys method. The analysis revealed that the primary cause stems from human error, particularly non-compliance with standard operating procedures (SOPs) and the absence of regular performance evaluations for pickers. As a corrective measure, a continuous improvement approach based on the Plan-Do-Check-Act (PDCA) cycle was designed.